Decay pattern of the Pygmy Dipole Resonance in 140Ce - Isaak J.; Löher B.; Savran D.; Aumann T.; Beller J.; Cooper N.; Derya V.; Duchêne M.; Endres J.; Fiori E.; Kelley J.H.; Knörzer M.; et al. (EPJ Web of Conferences, 2015)
The decay behavior of low-lying dipole states in 140Ce was investigated exploiting the γ3-setup at the HIγS facility using quasi-monochromatic photon beams. Branching ratios of individual excited states as well as average branching ratios to low-lying states have been extracted using γ – γ coincidence measurements. The comparison of the average branching ratios to QPM calculations shows a remarkable agreement between experiment and theory in the energy range from 5.0 to 8.5 MeV.